IMPLEMENTASI PCI-DSS UNTUK KEAMANAN DATA KARTU PEMBAYARAN PADA PT DHARMA LAUTAN NUSANTARA - Fahrizal Fahrizal; Ade Surya Budiman; Muhammad Rifqi Anuar (Institut Teknologi dan Bisnis Swadharma, 2022)
The quality of service provided by the company must be maintained including providing transaction facilities using a secure credit card so that it can provide the best to customers and aims to increase the sense of trust in the company in making payments using credit cards. The method used to improve information security and corporate networks is to implement network security in accordance with the Payment Card Industry Data Security Standard (PCI-DSS) standard. The method used in this study is to identify data and communications that are the focus of security in compliance with PCI DSS, reduce the scope of security by implementing network segmentation by determining the classification of devices, communication lines and people into three categories based on the presence or absence of a relationship to data. credit cards, namely Cardholder Data Environment (CDE), Shared Network and Corporate Local Area Network. (LAN) Then manage the data communication traffic between the three segments according to compliance with the PCI DSS standard.